2020
DOI: 10.1177/1971400920953417
|View full text |Cite
|
Sign up to set email alerts
|

MRI predictors for brain invasion in meningiomas

Abstract: Background and purpose In the 2016 revision of the World Health Organization classification of central nervous system tumours, brain invasion was added as an independent histological criterion for the diagnosis of a World Health Organization grade II atypical meningioma. The aim of this study was to assess whether magnetic resonance imaging characteristics can predict brain invasion for meningiomas. Materials and methods We conducted a retrospective review of all meningiomas resected at our institution between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…In addition, peritumoral oedema was significantly different between the brain invasion and non-invasion groups. After LASSO analysis, there was a strong correlation between peritumoral oedema and brain invasion, which was consistent with the results of previous studies [ 6 , 28 , 30 ]. Several authors have reported a strong correlation between an invasive growth pattern and peritumoral oedema, and Mantle et al found a 20% increase in brain invasion incidence for each centimetre of oedema [ 11 ], while Gill et al reported that every 1-cm 3 increase in peritumoral oedema was associated with a 10% increase in the odds of brain invasion [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, peritumoral oedema was significantly different between the brain invasion and non-invasion groups. After LASSO analysis, there was a strong correlation between peritumoral oedema and brain invasion, which was consistent with the results of previous studies [ 6 , 28 , 30 ]. Several authors have reported a strong correlation between an invasive growth pattern and peritumoral oedema, and Mantle et al found a 20% increase in brain invasion incidence for each centimetre of oedema [ 11 ], while Gill et al reported that every 1-cm 3 increase in peritumoral oedema was associated with a 10% increase in the odds of brain invasion [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our result demonstrated that the irregular tumour shape corresponded to an “invasive” phenotype [ 27 ] and tended to grow in all directions at different rates. However, Ong et al reported that brain invasion was not associated with tumour contour [ 28 ]. This discrepancy could be attributed to the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, only peritumoral edema remained as an independent predictor of brain invasion in the multivariate analysis [41]. The predictive effect of peritumoral edema was later confirmed in other studies [42,43]. Parenchymal edema adjacent to the meningioma interface seems to be an expression of close interaction of the tumor with bordering structures, such as damage to the cortex by an infiltrating tumor.…”
Section: Imaging Aspects Of Invasive Growthmentioning
confidence: 53%
“…Alternatively, in the preoperative diagnosis/assessment, magnetic resonance imaging (MRI) is the most important technique for brain meningioma by taking advantage of its ultra-high tissue resolution and spatial resolution. Previous existing documents suggested that traditional MRI findings, like peri-tumoral edema, heterogeneous contrast enhancement, and irregular tumor shape, have values in predicting brain invasion (6,7). However, the outcomes of these imaging signs are not widely supportive (8), which may be resulting from the limited and insufficient information they provided.…”
mentioning
confidence: 99%